Randomized Controlled Trials In Pediatric Critical Care: Advancing The Research Enterprise - Duffett, Mark (My University, 2016)
Importance: Evidence from randomized controlled trials (RCTs) is required to guide treatment of critically ill children. Unfortunately such evidence is not always available. Objectives: To describe the RCT research enterprise in pediatric critical care — the evidence and the process of creating it, along with problems and some solutions. Methods: To meet these objectives I undertook a series of 5 related studies. First a scoping review to describe the output of the research enterprise. Second, a social network analysis of coauthorship patterns to describe the community of researchers who produce this evidence. Third, a survey to investigate the importance of RCTs in clinicians’ decision-making. Fourth, a survey of trialists to identify barriers and facilitators of high quality RCTs. Fifth, a qualitative interview study to identify acceptable, feasible and effective strategies to improve the evidence available from RCTs in pediatric critical care. Results and conclusions: The number of RCTs in pediatric critical care is increasing but there is a preponderance of small, single-centred RCTs focusing on laboratory or physiological outcomes that are often stopped early because of feasibility problems or futility. The research community is highly fragmented and highly clustered. Experienced trialists identified approaches to improve the pediatric critical care research enterprise, including building a sense of community and ensuring key training and relevant practical experiences for new investigators. Because of the barriers that researchers face and their ethical obligation to undertake trials that are feasible and make a meaningful contribution to advancing the care of critically ill children, individuals and groups must take an active role in building a healthy research community. Only by changing how we function as a research community can we train the next generation of investigators and undertake the type of trials needed to improve the care of critically ill children.
Keywords: pediatric critical care; pediatric intensive care; RCT; randomized controlled trials